The Use of the Adaptive Governance Model in the Implementation of Information Disclosure in the Government of South Sumatra - Amrullah; M. Sobri; Andries Lionardo; Raniasa Putra (GoAcademica Research & Publishing, 2023)
Information is a basic need for everyone both in order to develop personal qualities and in order to live their social life. The information needs of the people of South Sumatra are regarding programs carried out by the Government and also other information related to the needs of the people of South Sumatra. Disclosure of information is one of the ways in which the Government of South Sumatra provides information rights to the public. This research uses a descriptive qualitative method where all information is not in the form of numbers but explanations. The conclusion of the research is that the Government of South Sumatra uses three (three) approaches in implementing adaptive governance, namely collaboration, flexibility, and learning.